US believed top Chinese leadership to have directed computer hackings. (Tibetan Review: The Monthly Magazine on all Aspects of Tibet, 2011)
The article reports on the allegation that top officials of the Chinese Politburo, including Li Changchun, have directed the hacking of computers of the U.S. government, its allies, and of the Dalai Lama of Tibet through Google. According to the "New York Times," the Chinese attacks against Google were part of a coordinated campaign of computer sabotage as mandated by the Chinese government. Officials of Google claim that China had managed to steal part of its source code.